Assessment of the Pig‐a, micronucleus, and comet assay endpoints in rats treated by acute or repeated dosing protocols with procarbazine hydrochloride and ethyl carbamate. (21st September 2018) - Chen, Gaofeng; Wen, Hairuo; Mao, Zhihui; Song, Jie; Jiang, Hua; Wang, Weifan; Yang, Ying; Miao, Yufa; Wang, Chao; Huang, Zhiying; Wang, Xue
Abstract : The utility and sensitivity of the newly developed flow cytometric Pig‐a gene mutation assay have become a great concern recently. In this study, we have examined the feasibility of integrating the Pig‐a assay as well as micronucleus and Comet endpoints into acute and subchronic general toxicology studies. Male Sprague–Dawley rats were treated for 3 or 28 consecutive days by oral gavage with procarbazine hydrochloride (PCZ) or ethyl carbamate (EC) up to the maximum tolerated dose. The induction of CD59‐negative reticulocytes and erythrocytes, micronucleated reticulocytes in peripheral blood, micronucleated polychromatic erythrocytes in bone marrow, and Comet responses in peripheral blood, liver, kidney, and lung were evaluated at one, two, or more timepoints. Both PCZ and EC produced positive responses at most analyzed timepoints in all tissue types, both with the 3‐day and 28‐day treatment regimens. Furthermore, comparison of the magnitude of the genotoxicity responses indicated that the micronucleus and Comet endpoints generally produced greater responses with the higher dose, short‐term treatments in the 3‐day study, while the Pig‐a assay responded better to the cumulative effects of the lower dose, but repeated subchronic dosing in the 28‐day study. Collectively, these results indicate that integration of several in vivo genotoxicity endpoints into a single routine toxicology study is feasible and that the Pig‐a assay may be particularly suitable for integration into subchronic dose studies based on its ability to accumulate the mutations that result from repeated treatments. This characteristic may be especially important for assaying lower doses of relatively weak genotoxicants. Environ. Mol. Mutagen. 60:56–71, 2019. © 2018 Wiley Periodicals, Inc.